2019
DOI: 10.15252/embr.201947961
|View full text |Cite
|
Sign up to set email alerts
|

Effector loading onto the VgrG carrier activates type VI secretion system assembly

Abstract: The type VI secretion system (T6SS) is used by many bacteria to engage in social behavior and can affect the health of its host plant or animal. Because activities associated with T6SSs are often costly, T6SSs must be tightly regulated. However, our knowledge regarding how T6SS assembly and contraction are regulated remains limited. Using the plant pathogen Agrobacterium tumefaciens, we show that effectors are not just passengers but also impact on T6SS assembly. The A. tumefaciens strain C58 encodes one T6SS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…This explanation is consistent with recent findings that effector loading onto its cognate VgrG spike activates T6SS assembly (Liang et al, 2019;Wu et al, 2020). This is also supported by data showing that the three last β-sheets of VgrG1b specifically interact with the cognate PAAR effector Tse7 (Shneider et al, 2013;Pissaridou et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This explanation is consistent with recent findings that effector loading onto its cognate VgrG spike activates T6SS assembly (Liang et al, 2019;Wu et al, 2020). This is also supported by data showing that the three last β-sheets of VgrG1b specifically interact with the cognate PAAR effector Tse7 (Shneider et al, 2013;Pissaridou et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our study highlights the fine balance between the functionality of the spike, e.g., its ability to perforate the cell envelope once embedded in the T6SS membrane complex and thus its delivery into the extracellular medium, and its capacity to bind a cargo effector and drive its secretion. Previous studies in Serratia marcescens, Acinetobacter baylyi, and A. tumefaciens demonstrated that at least one VgrG protein and its cognate PAAR need to assemble to form a functional T6SS tip (Shneider et al, 2013;Bondage et al, 2016;Cianfanelli et al, 2016;Wu et al, 2020). In the case of S. marcescens, three such assemblies can form: VgrG1 and its cognate PAAR; VgrG2 and Rhs1 or VgrG2 and Rhs2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this course of study, our group also discovered that Tde effector loading onto VgrG is critical for T6SS assembly and Hcp secretion (Wu et al, 2019a). Thus, aside from expressing G2 C58 or Ga 1D1609 in C58 tdei G1 G2op donor strain, a plasmid expressing Tde2 with catalytic site mutation and its cognate DUF2169 chaperone/adaptor (pTde2 M ) was also included to ensure effective T6SS assembly and firing.…”
Section: Vgrg Can Be Exchanged Between C58 and 1d1609mentioning
confidence: 99%
“…Besides T4SS, T6SS is also widespread in A. tumefaciens species with a conserved function for interbacterial competition (6)(7)(8)(9). A. tumefaciens strain C58 has been used as a model for studying T6SS because of its completed genome and wellestablished genetic tools and resources (10) (11) or distantly related Escherichia coli in vitro (12). However, the level of antibacterial activity is relatively modest (about 0.5 to 1 log 10 ) and far behind to other T6SS-containing bacteria such as V. cholera and P. aeruginosa (> 3 log 10 colonyforming-unit [cfu] inhibition of E. coli) (13,14), although P. aeruginosa is not active against E. coli unless provoked, known as tit-for-tat (15).…”
Section: Introductionmentioning
confidence: 99%